Russia's Technological Sovereignty: Research and Modeling from the Standpoint of System Transformation of the Economy - Nikonova Alla (π-Economy, 2023)
Relevance. The problem of technological sovereignty is being explored in the context of sanctions against Russia. The goal is to form an approach to balanced solutions in ensuring technological sovereignty in end-to-end technologies through domestic R&D and intellectual potential. Methodology and methods. The provisions of the system economic paradigm are used as the basis of the system analysis and synthesis of the Russian economy, modeling the interactions of key sectors of the social system, and formulating conclusions. Results. A significant degree of dependence both on foreign technologies and on other components of imports is presented in dynamics and in the context of activities. The possibilities and limitations of Russia's technological sovereignty in relation to the field of information technology as one of the critical ones are given. Two scenarios of technological sovereignty are considered: import substitution and a radical transformation of the economic model as a whole. For this, simulation models are presented. Novelty. Structural and functional models based on platform solutions in the field of IT imitate the interactions of enterprises searching for technologies within a system that includes not three, but four collective actors. Unlike traditional approaches, the division of economy on the business and enterprise sector, which differ in goals (profit and continuity of the reproduction cycle), allows you to avoid the dominance of any one goal in ensuring technological sovereignty, to overcome the contradiction between short-term and long-term goals. The results of a systematic approach lead to network structures without loss of functionality in conditions of limited resources, provide scientific knowledge about the importance of collaboration between actors as a fundamental factor in the transformation of the economic model and technological sovereignty in the long term. Conclusions. Collaborative forms of interaction serve as a means of self-organization and formation of innovative ecosystems. A systematic view of the structure and functions of actors contributes to the development of balanced economic, institutional, organizational measures to ensure technological sovereignty and increase their validity. The tetrad representation of the functions of the four actors allows us to explore ways to obtain end-to-end technologies not only in the field of IT; this also applies to further research on the topic of Russia's technological sovereignty.